Do the Right Thing: Experimental evidence that preferences for moral behavior, rather than equity or efficiency per se, drive human prosociality - Capraro, Valerio; Rand, David G. (Judgment and Decision Making, 2018)
Decades of experimental research show that some people forgo personal gains to benefit others in unilateral anonymous interactions. To explain these results, behavioral economists typically assume that people have social preferences for minimizing inequality and/or maximizing efficiency (social welfare). Here we present data that cannot be explained by these standard social preference models. We use a ＂Trade-Off Game＂ (TOG), where players unilaterally choose between an equitable option and an efficient option. We show that simply changing the labelling of the options to describe the equitable versus efficient option as morally right completely reverses the correlation between behavior in the TOG and play in a separate Dictator Game (DG) or Prisoner's Dilemma (PD): people who take the action framed as moral in the TOG, be it equitable or efficient, are much more prosocial in the DG and PD. Rather than preferences for equity and/or efficiency per se, our results suggest that prosociality in games such as the DG and PD are driven by a generalized morality preference that motivates people to do what they think is morally right.